La agencia del estudiante como factor central en el aprendizaje de inglés como lengua extranjera en un entorno virtual: un análisis de la interacción - Rojas, Daniel (2023)
The COVID-19 pandemic brought about new challenges for class interaction and for English as a Foreign Language teaching instruction in general, and opened a whole world of opportunities to learn about virtual-mediated instruction and about learning altogether. As a reaction to the new social conditions, alternative spaces, and ways of mediating instruction through the use of technology and digital resources were created and promoted in the quest for teaching and learning. As such, this multimodal interaction analysis inquired into the qualities of interaction taking place in an online course of advanced English at a teaching credential undergraduate program at a private university in Bogotá, and the affordances and limitations that such interactions presented for agency, engagement, and ultimately, learning as an effect of communication. To such an end, class observations, student focus groups, and interviews on teachers were conducted. The findings offered insights on the multiple ways students and the teacher resorted to their semiotic resources and communicative modes to configure meaning, construct knowledge, and relate to one another in a virtual environment. Mainly, however, it encourages a debate about the role that teachers play in designing and implementing communicative environments to enrich the teaching and learning experience.